Assessing the Soil Carbon Sequestration Potential of Different Plant Residues - Amon, N.K. (University of Ghana, 2006)
This study investigated the use o f fallow residue management as a means o f sequestering soil carbon to mitigate the build up o f atmospheric carbon dioxide. The study involved the analysis o f the effect o f three soil moisture levels (W l= Field Capacity (FC), W2 = 70% FC and W3 = 40 % FC) on the decomposition rate o f five different fallow plant residues.(i) Pennisetum spp (elephant grass) from natural bush fallow, RT1, (ii) Cajanus cajan (pigeon pea) residue, RT2, (iii) Vigna unguiculata (cowpea), RT3, (iv) Mucuna pruriens (mucuna) residue, RT4 and (v) Pennisetum spp (elephant grass which had benefited from residual fertilizer) under greenhouse conditions. The residues were incubated for 180 days in potted soils (Haplic Lixosols) and monitored over a 6 -month period and the amount o f organic carbon added to the soil was determined. Limited study o f residue decomposition under field conditions was also carried out and compared with the greenhouse conditions. Results showed that water had a significant effect (P<0.05) on the decomposition rates o f plant residues. The order o f water treatment on the decomposition o f plant residues generally was: W1 > W2 > W3. Decomposition was also different for the residue types in the order: RT1 < RT5 < RT3 < RT4 < RT2. This study showed that the grasses; R T la n d RT5 having h igh C:N ratios were b etter contributors to soil carbon storage. It was also observed that at the end o f the incubation period all the plant residues added significantly higher carbon to the soil than the control. (RT6 ). A similar response was also observed in the field even though water and temperature could not be controlled. A simple equation developed to describe the variation o f residue decomposition with soil water gave reasonable predictions o f residue weight loss with time. It is concluded that residue type and soil moisture management offer measures for improving soil carbon sequestration in tropical agricultural systems.
Thesis(M.Phil)-University of Ghana, 2006